Design Of Automatic Citrus Fertilizer Irrigation System Based On Photocell Timer - Hariandi, Yusuf; Ginting, Dianta (Universitas Mercu Buana, 2025)
Climate has a significant influence on nearly all aspects of plant growth, including that of citrus plants. To overcome the uncertain environment, a reliable irrigation system is essential in citrus gardens, with optimization achieved through the use of an automated irrigation system. The engineering of this automatic citrus garden fertilization irrigation system is carried out in groups on citrus plants using a photocell timer and PVC stop valve on each plant group path to facilitate maintenance and repairs if damage occurs to the automatic irrigation system without disrupting the main pipe irrigation system and other plant groups. This automatic irrigation system, in the driving engine and sprayer pump section, utilizes a machine and a sprayer pump with spare parts readily available in each region, thereby facilitating maintenance and repairs as needed. The machine and sprayer pump function to pump water and fertilizer that have previously been mixed in the mixing tank. Then the water and fertilizer will be distributed through the main pipe distribution line and the fertilization system pipe in groups using ½ inch PVC pipes and using a sprayer hose to the citrus trees. Engineering an automatic citrus fertilization irrigation system and processing carried out in groups on citrus plants will speed up the work of farmers in the garden, so that it can be more effective and more efficient, and save labor